The Effect of Product Innovation and Promotion on Purchasing Decisions at Historia Cafe and Royal Kitchen Manna Bengkulu Selatan - Oky Anggara; Ida Anggriani; Abdul Rahman (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Producers need to understand consumer behavior towards products or brands that are on the market, because the nature of consumers who are never satisfied makes producers have to be more innovative and creative, then various ways need to be done to make consumers interested in the products produced. This study aims to determine the effect of product innovation and promotion on purchasing decisions at Historia Cafe and Royal Kitchen Manna of South Bengkulu. Samples in this study were 100 customers who purchased food and beverages at Historia Cafe and Royal Kitchen Manna of South Bengkulu. Data collection used a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed Y = 8.737 + 0.464X1 + 0.354 X2, + 3.581 this illustrates a positive regression direction, meaning that there is a positive influence between X1 (product innovation) and X2 (promotion) on purchasing decisions (Y). Means that if the product innovation and promotion variables increase, it will increase purchasing decisions. The magnitude of the coefficient of determination is 0.496. This means that X1 (product innovation) and X2 (promotion) influence the purchase decision (Y) by 49.6% while the remaining 50.4% is influenced by other variables not examined in this study. The results of the t test at a significance level of 0.05 explain that partially the product innovation and promotion variables have a significant influence on the purchasing decision variable at Historia Cafe and Royal Kitchen Manna of South Bengkulu. The results of the F test at a significance level of 0.05 explain that the product innovation and promotions have a simultaneous (together) influence on purchasing decisions at Historia Cafe and Royal Kitchen Manna of South Bengkulu